Parallel enrollments: associations between university student life and performance - Alexander Karl Ferdinand Loder; Amani Colleen Brandweiner; Guilherme Maia de Oliveira Wood (Cogent Education)
Austria’s university system has no tuition fees and allows students to enroll in an unlimited number of programs simultaneously, regulated via legal measures to ensure fast and efficient studying and especially challenging those with more than one enrollment. The aim of this study was to identify associations between student performance and dimensions of student life. The sample consisted of 213 students, filling in an online survey; 48 respondents had multiple enrollments. Objective performance from a university’s database were merged with survey data. Regression analyses were conducted on the levels 1) full dataset, 2) students with one enrollment and 3) students with multiple enrollments. Average grades and failed exams were negatively associated with sleep for students with one enrollment, but not with multiple enrollments. Performance of multiple enrollment students cannot be explained the same way as for students with one enrollment. There is a difference between these student groups in which variables are associated with student performance. Implications are that a university system allowing for multiple enrollments needs targeted support structures to address the differences between these student groups. More research is needed on which support mechanisms can be introduced to specifically target students with multiple enrollments.